Particulate Alum via Pickering Emulsion for an Enhanced COVID‐19 Vaccine Adjuvant. Issue 40 (30th August 2020) - Peng, Sha; Cao, Fengqiang; Xia, Yufei; Gao, Xiao‐Dong; Dai, Lianpan; Yan, Jinghua; Ma, Guanghui
Abstract: For rapid response against the prevailing COVID‐19 (coronavirus disease 19), it is a global imperative to exploit the immunogenicity of existing formulations for safe and efficient vaccines. As the most accessible adjuvant, aluminum hydroxide (alum) is still the sole employed adjuvant in most countries. However, alum tends to attach on the membrane rather than entering the dendritic cells (DCs), leading to the absence of intracellular transfer and process of the antigens, and thus limits T‐cell‐mediated immunity. To address this, alum is packed on the squalene/water interphase is packed, forming an alum‐stabilized Pickering emulsion (PAPE). "Inheriting" from alum and squalene, PAPE demonstrates a good biosafety profile. Intriguingly, with the dense array of alum on the oil/water interphase, PAPE not only adsorbs large quantities of SARS‐CoV‐2 (severe acute respiratory syndrome coronavirus 2) antigens, but also harbors a higher affinity for DC uptake, which provokes the uptake and cross‐presentation of the delivered antigens. Compared with alum‐treated groups, more than six times higher antigen‐specific antibody titer and three‐fold more IFN‐γ‐secreting T cells are induced, indicating the potent humoral and cellular immune activations. Collectively, the data suggest that PAPE may provide potential insights toward a safe and efficient adjuvant platform for the enhanced COVID‐19 vaccinations. Abstract : The adjuvant‐effect of the licensed alum adjuvant by particulate alum via Pickering emulsion (PAPE) is exploited toward enhanced COVID‐19 vaccines. PAPE mirrors and "inherits" the acknowledged biosafety profile. Additionally, the alum‐packed interphase confers higher affinity for dendritic cell uptake, which provokes the uptake and cross‐presentation of antigens for potent humoral and cellular responses.